2018
DOI: 10.3389/fvets.2018.00035
|View full text |Cite
|
Sign up to set email alerts
|

The Unexplored Role of Intra-articular Adipose Tissue in the Homeostasis and Pathology of Articular Joints

Abstract: Intra-articular adipose tissue deposits known as articular fat pads (AFPs) are described to exist within synovial joints. Their assumed role in normal joint biomechanics is increasingly objectivized by means of advanced methods of functional imaging. AFPs possess structural similarity with body subcutaneous white adipose tissue (WAT), however, seems to be regulated by independent metabolic loops. AFP dimension are conserved during extreme WAT states: obesity, metabolic syndrome, lipodystrophy, and cachexia. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 60 publications
0
26
0
1
Order By: Relevance
“…The biomechanical and homeostatic role of synovial fat tissue and synovial adipocytes remains incompletely understood (8). At the molecular level, adipocytes in synovial tissue may play multiple critical roles in maintaining healthy joints, including energy metabolism and maintaining the stem cell niche (25). Adipocytes secrete both proinflammatory (such as TNF, IL6, IL8) and anti-inflammatory adipokines and cyto-kines (11,24,33).…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical and homeostatic role of synovial fat tissue and synovial adipocytes remains incompletely understood (8). At the molecular level, adipocytes in synovial tissue may play multiple critical roles in maintaining healthy joints, including energy metabolism and maintaining the stem cell niche (25). Adipocytes secrete both proinflammatory (such as TNF, IL6, IL8) and anti-inflammatory adipokines and cyto-kines (11,24,33).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the influences of antirheumatic drugs on dominant potential factors for articular regenerative, the effects of these drugs on adipogenic induction is of interest. Although it has been hypothesized that synovial adipocytes may contribute to maintenance of articular energy metabolism and the stem cell niche, the precise role of adipocytes in the regulation of cartilage homeostasis remains poorly understood (Labusca and Zugun-Eloae, 2018). Direct application of methotrexate downregulated the expression of FABP4 in a dose-dependent manner, whereas prednisolone only slightly inhibited FABP4 induction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in addition to reducing mechanical forces, the Hoffa fat pad, as well as other fat pad within the body, serves a proprioceptive role. 2…”
Section: Imaging Anatomy Of the Lateral Kneementioning
confidence: 99%